Territoriality modifies the effects of habitat complexity on animal behavior: a meta-analysis. (8th February 2022) - Church, Kathleen D W; Matte, Jean-Michel; Grant, James W A
Abstract: Augmenting habitat complexity by adding structure has been used to increase the population density of some territorial species in the wild and to reduce aggression among captive animals. However, it is unknown if all territorial species are affected similarly by habitat complexity, and whether these effects extend to non-territorial species. We conducted a meta-analysis to compare the behavior of a wide range of territorial and non-territorial taxa in complex and open habitats to determine the effects of habitat complexity on 1) territory size, 2) population density, 3) rate and time spent on aggression, 4) rate and time devoted to foraging, 5) rate and time spent being active, 6) shyness/boldness, 7) survival rate, and 8) exploratory behavior. Overall, all measures were significantly affected by habitat complexity, but the responses of territorial and non-territorial species differed. As predicted, territorial species were less aggressive, had smaller territories and higher densities in complex habitats, whereas non-territorial species were more aggressive and did not differ in population density. Territorial species were bolder but not more active in complex habitats, whereas non-territorial species were more active but not bolder. Although the survival of non-territorial species increased in complex habitats, no such increase was observed for territorial species. The increased safety from predators provided by complex habitats may have been balanced by the higher population densities and bolder behavior in territorial species. Our analysis suggests that territorial and non-territorial animals respond differently to habitat complexity, perhaps due to the strong reliance on visual cues by territorial animals. Abstract : The behavioural response to habitat complexity differs for territorial and non-territorial animals. Territorial species are less aggressive, have smaller territories and are more abundant, while non-territorial species show higher activity and more aggression in response to habitat complexity. Additionally, the expected decrease in predation risk in complex habitats was observed for non-territorial animals but not for territorial animals.